Performance analysis of Z-channel with relay under Rayleigh fading and discrete constellations - Sirigina, Rajendra Prasad. (2013)
Interference forwarding in an interference channel makes the interference stronger which in turn enables the usage of simple detectors like the successive interference canceler (SIC) at the destinations. In this paper, detect and forward (DF), amplify and forward (AF) based interference forwarding protocols (also called as AF-SIC and DF-SIC protocols) are analyzed. Symbol error rate (SER) performance of the SIC, AF-SIC and DF-SIC protocols using M-PAM modulation is studied. Also the relay channel gains required to restore full diversity for the AF-SIC and the DF-SIC protocols are obtained. Impact of the relay power and relay location on the SER performance is also studied. The proposed protocols are proved to provide the same SER performance as the orthogonal transmission scheme while improving the spectral efficiency.